2017
DOI: 10.1007/s11051-017-3966-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a particle tracking analysis method for the size determination of nano- and microparticles

Abstract: Particle tracking analysis (PTA) is an emerging technique suitable for size analysis of particles with external dimensions in the nano- and sub-micrometre scale range. Only limited attempts have so far been made to investigate and quantify the performance of the PTA method for particle size analysis. This article presents the results of a validation study during which selected colloidal silica and polystyrene latex reference materials with particle sizes in the range of 20 nm to 200 nm were analysed with NS500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 22 publications
2
79
0
Order By: Relevance
“…The dynamic light scattering (DLS) technique is usually performed to find the size of nanoparticles in dispersion . The hydrodynamic diameter, PDI and zeta potential of the particles can be determined by this technique.…”
Section: Characterizing the Nanoparticles/microparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic light scattering (DLS) technique is usually performed to find the size of nanoparticles in dispersion . The hydrodynamic diameter, PDI and zeta potential of the particles can be determined by this technique.…”
Section: Characterizing the Nanoparticles/microparticlesmentioning
confidence: 99%
“…Assumed to be an accurate technique to measure size, with less interference of particle aggregates than in DLS, particle tracking analysis is used for both nanoparticles and microparticles . This technique can also be used to count particles, which is a feature not present in DLS .…”
Section: Characterizing the Nanoparticles/microparticlesmentioning
confidence: 99%
“…SPT can be an efficient and thorough technique for the study of polydisperse nanomaterial samples as particles of disparate sizes can be observed and studied simultaneously without bias. To this end, commercial SPT instruments were developed to size particles of the nanometer range …”
Section: Introductionmentioning
confidence: 99%
“…To this end, commercial SPT instruments were developed to size particles of the nanometer range. [28] In this contribution, we perform SPT on a series of dispersions and analysis using Maximum A posteriori Nanoparticle Tracking Analysis (MApNTA), [29] a new Bayesian method developed in our laboratory for estimation of the PSD. Commonly produced nanoparticles were explored, including single-walled carbon nanotubes (SWCNT) dispersed using a variety of agents such as ss(GT) 15 -DNA and SDS.…”
Section: Introductionmentioning
confidence: 99%
“…(NTA), generally consists of sample preparation, video recording and video analysis, equipped with a sample chamber with a 640-nm laser and a Viton Fluor elastomer Oring. Sample preparation often requires diluting the supplied sample in an aqueous medium such as purified water until the particle concentration is within the recommended range of 10 7 to 10 9 particles/mL 16 . The samples were injected in the sample chamber with normal syringe until the liquid reached the tip of the nozzle 15 .…”
Section: Characterization Of Nanoparticles: Determination Of the Partmentioning
confidence: 99%